The Chinese Managers' Perception of the Market Orientation: To What Extent Do Western Ideas of Marketing Matter? - Zhang, Huijun (2007)
The market orientation concept has been developed many years in western countries. Besides, organizations of western countries have implemented the market orientation applications. Recently, many theorists find out that the market orientation concept may be applied to other countries. This dissertation aims to find out the Chinese managers perception of the market orientation.